Cutoff criteria for overall model fit indexes in generalized structured component analysis - Gyeongcheol Cho; Heungsun Hwang; Marko Sarstedt; Christian M. Ringle (Journal of Marketing Analytics, 2020)
Generalized structured component analysis (GSCA) is a technically well-established approach to component-based structural equation modeling that allows for specifying and examining the relationships between observed variables and components thereof. GSCA provides overall fit indexes for model evaluation, including the goodness-of-fit index (GFI) and the standardized root mean square residual (SRMR). While these indexes have a solid standing in factor-based structural equation modeling, nothing is known about their performance in GSCA. Addressing this limitation, we present a simulation study's results, which confirm that both GFI and SRMR indexes distinguish effectively between correct and misspecified models. Based on our findings, we propose rules-of-thumb cutoff criteria for each index in different sample sizes, which researchers could use to assess model fit in practice.
Keywords: 650; Component-based structural equation modeling; Generalized structured component analysis; Model fit; GFI; SRMR